Analysis Of Village Resources In Realizing Sustainable Village Development: A Case Study Of Bontorappo Village, Arungkeke Village And Pattiro Village, Jeneponto Regency, South Sulawesi - Widyawati Widyawati; Nimrah Rahmayanti Yusuf; Sulmiah Sulmiah (Program Pascasarjana Universitas Negeri Makassar, 2022)
The government's policy regarding the implementation of sustainable village development is an effort to accommodate the application of local wisdom in the implementation of development, and as a strategy to achieve 74% of the implementation of the national SDGs. This policy is determined by looking at the potential resources owned by the village. This research will analyze village resources in supporting the realization of sustainable village development. The research data is not only sourced from information obtained from interviews but is supported by the results of studies from various kinds of literature such as regulations and journals as well as observations. The data obtained, after going through the analysis and triangulation process, shows that the government's belief in village resources can realize sustainable village development has not been proven. Human resources as the key to successful development have many shortcomings in terms of governance, knowledge, and skills. The Village Government cannot take advantage of its potential to increase income. The development carried out so far only supports approximately 45% of the sustainable village development goals. The government needs to maximize efforts to build village government capacity so that the objectives of sustainable village development policies can be achieved.